(untitled) (Journal for Studies in Humanities and Social Sciences, 2020)
The education sector in Namibia experiences challenges such as imbalanced learner-teacher ratios, poor working conditions, lack of resources and criticisms from the Ministry of Education, Arts and Culture and parents because of high failure rates. Organisational commitment is the psychological link that employees have in wanting to remain with and exert significant efforts on behalf of an organisation. Relationships have been confirmed between authentic leadership (leaders who are genuine and stand up for their followers), perception of fairness and equity within the workplace, psychological conditions and organisational commitment. A cross-sectional survey design was used to collect data on authentic leadership, organisational justice, psychological conditions and organisational commitment of teachers from the Omaheke, Oshana and Oshikoto regions in Namibia (n=288). The data were analysed using SPSS (24.0) with Pearson product-moment correlation and multiple regression analyses to assess the impact of these variables on organisational commitment of teachers. The significant predictors of organisational commitment were the openness and transparency of leaders; how they share information freely; their engagement in moral and ethical behaviour; and when teachers experience interactional justice and psychological meaning in their work. This study proposes leadership development to enhance transparency of leaders, development and implementation of policies ensuring just and fair interactions between superiors and subordinates as well as re-evaluation of remuneration and compensation packages to enhance the level of meaningfulness experienced by teachers.